Pengaruh Nilai Budaya Lokal, Nilai Sosial, Dan Locus Of Control Terhadap Kapatuhan Wajib Pajak Orang Pribadi Di KPP Pratama Makassar Selatan - Atia Kirana; Ulfa Rabiyah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
This study aims to analyze the influence of local cultural values, social values, and locus of control on individual taxpayer compliance at KPP Pratama Makassar Selatan. This study uses primary and secondary data, primary data obtained through data from the answers of each respondent and secondary data obtained from KPP Pratama South Makassar related to the number of registered individual taxpayers, taxpayers who are required to SPT, and the number of taxpayers who report SPT. The sample in this study were 100 individual taxpayers registered at the South Makassar KPP Pratama. The research instrument used was a questionnaire using a five-level Likert scale. In this study, the researcher took the Simple Random Sampling technique, namely the random sampling so that it was not limited but could represent the entire population. Data analysis and hypothesis testing were carried out using the Multiple Linear Regression Analysis technique. The results of the research that have been carried out have found that local cultural values, social values, and locus of control partially or simultaneously have a positive and significant impact on individual taxpayer compliance at KPP Pratama South Makassar. The results of the determination coefficient test obtained that the adjusted R square value was 0.506. This shows that 50.6% of the individual taxpayer compliance variables will be influenced by the independent variables, namely local cultural values (x1), social values (x2), and locus of control (x3) and the remaining 40.4% of taxpayer compliance variables individual will be influenced by other variables not discussed in this study.